1995
DOI: 10.1139/x95-060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated moose browsing on growth, mortality, and fecundity in Scots pine: relations to plant productivity

Abstract: Current theory on plant–animal interactions predicts that the outcome of herbivory on plant performance will be dependent on plant productivity. Thus, slow-growing plants should be less able to compensate for biomass losses than fast-growing plants, and therefore be more susceptible to herbivory if attacked. We simulated winter browsing by moose (Alcesalces (L.)) on Scots pine (Pinussylvestris L.) along a gradient of plant productivity and addressed the following questions: (1) Does herbivory affect growth ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 0 publications
4
39
0
2
Order By: Relevance
“…Nadelbaumarten, mit Ausnahme der Lärche, zeigen diese Reaktion nur sehr begrenzt (Eiberle 1975). Während einmaliger leichter Verbiss offenbar kompensiert werden kann (Cunningham et al 2006), ist die Fähigkeit vieler Nadelbaumarten, Triebe nach mehrmaligen Verbiss oder einmaligen starken Verbiss zu regenerieren, gering (Edenius et al 1995, Hódar et al 2008. Entsprechend erwiesen sich in den Untersuchungen von Weise (1997) durch simulierten Verbiss verursachte Höhenwachstums-und Durchmesserwachstumsreduktionen als dauerhaft.…”
Section: Reaktion Auf Schädigungenunclassified
“…Nadelbaumarten, mit Ausnahme der Lärche, zeigen diese Reaktion nur sehr begrenzt (Eiberle 1975). Während einmaliger leichter Verbiss offenbar kompensiert werden kann (Cunningham et al 2006), ist die Fähigkeit vieler Nadelbaumarten, Triebe nach mehrmaligen Verbiss oder einmaligen starken Verbiss zu regenerieren, gering (Edenius et al 1995, Hódar et al 2008. Entsprechend erwiesen sich in den Untersuchungen von Weise (1997) durch simulierten Verbiss verursachte Höhenwachstums-und Durchmesserwachstumsreduktionen als dauerhaft.…”
Section: Reaktion Auf Schädigungenunclassified
“…We did not consider the habitats pine and yew in the case of saplings because very few saplings were found growing under these tree species, and all of them were simultaneously growing under¯eshy-fruited shrubs (and, thus, were classi®ed under this category). In addition, we estimated the age of the saplings as the number of whorls of the main shoot [for this procedure with other conifers, see Edenius et al (1995);]. …”
Section: Spatial Distribution Of Saplingsmentioning
confidence: 99%
“…Gong et al [12] reported that in native pinewoods at Glen Tanar, Aberdeenshire (Scotland), the dominant seedlings, defined as the tallest 10 percent of seedlings in each plot, when aged 12 (61.5 cm height) were 22 cm higher in fenced than in unfenced plots. Slow-growing Scots pine plants are less able to compensate for biomass losses and, therefore, they have less chances to survive when attacked [8]. In consequence, damage is more detrimental in poor sites, thus increasing regeneration difficulties.…”
Section: Main Factors Affecting Density Of Seedlingsmentioning
confidence: 99%